Low-leverage policy dynamics: An empirical analysis - Ferrão, J.; Curto, J. D.; Gama, A. P. (Review of Accounting and Finance, 2016)
Purpose - The purpose of this paper is to provide new insights into the low-leverage phenomenon by analyzing the dynamics of firms' financing policies. The authors explore three theoretical explanations of firms' motivations to switch among different levels of debt aversion: financial constraints, financial flexibility and financial distress. Design/methodology/approach - The authors apply a multilevel mixed-effects model to a panel data sample of 9,005 US listed firms during 1987-2014. To use a multinomial ordered logit model, the authors break down the low-leverage firms into several levels of debt aversion. Findings - The empirical analysis provides four main findings. First, there is a dynamic behavior regarding leverage policy: after five years, 39.4 per cent of initial zero debt firms remain all-equity firms, 14.2 per cent are leveraged firms and approximately 19.7 per cent still adopt a low-leverage policy. Second, greater asset volatility increases the expected likelihood that firms will be debt averse. Third, when firms grow bigger and older, they show a greater likelihood of moving toward a higher leverage level. Fourth, results derived from the investment variables of research and development, acquisitions, and capital expenditure provide strong evidence in favor of the financial flexibility hypothesis. Practical implications - These findings suggest that conservative debt policy is integrated with corporate investment decisions. Originality/value - This paper contributes to extant literature by emphasizing the dynamic process associated with a low-leverage policy, unlike prior studies that focus on the determinants and characteristics of low-leverage firms. It also applies an econometric methodology that is new to the field: multilevel models.